2018
DOI: 10.5194/acp-2018-785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cloud feedbacks in extratropical cyclones: insight from long-term satellite data and high-resolution global simulations

Abstract: <p><strong>Abstract.</strong> Extratropical cyclones provide a unique set of challenges and opportunities in understanding variability in cloudiness over the extratropics (poleward of 30°). We can gain insight into the shortwave cloud feedback from examining cyclone variability. Here we contrast global climate models (GCMs) with horizontal resolutions from 7 km up to hundreds of kilometers with Multi-Sensor Advanced Climatology Liquid Water P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Although investigation of the physical processes responsible for the contribution of ice and liquid clouds to d ln 𝜏 dT (second and third terms on the RHS of equation ( 5), respectively) is beyond the scope of this study, these terms are nevertheless shown to put the contribution of thermodynamic phase shifts to d ln 𝜏 dT (first term on the RHS of equation ( 5)) in context. Processes related purely to liquid clouds include but are not limited to changes in adiabatic water content, moisture fluxes into the warm conveyor belt (McCoy et al, 2019), precipitation, cloud-top entrainment, and other processes related to boundary-layer decoupling for low clouds. Some processes related to ice clouds include precipitation, riming, ice nucleation, and ice splintering.…”
Section: Decomposition Of Cloud Optical Depth Variations With Tempera...mentioning
confidence: 99%
“…Although investigation of the physical processes responsible for the contribution of ice and liquid clouds to d ln 𝜏 dT (second and third terms on the RHS of equation ( 5), respectively) is beyond the scope of this study, these terms are nevertheless shown to put the contribution of thermodynamic phase shifts to d ln 𝜏 dT (first term on the RHS of equation ( 5)) in context. Processes related purely to liquid clouds include but are not limited to changes in adiabatic water content, moisture fluxes into the warm conveyor belt (McCoy et al, 2019), precipitation, cloud-top entrainment, and other processes related to boundary-layer decoupling for low clouds. Some processes related to ice clouds include precipitation, riming, ice nucleation, and ice splintering.…”
Section: Decomposition Of Cloud Optical Depth Variations With Tempera...mentioning
confidence: 99%
“…Liquid clouds within this environment respond to large‐scale meteorological forcing and moisture transports (Field & Wood, 2007; Govekar et al., 2011; Kelleher & Grise, 2019; Klein et al., 2017; D. T. McCoy et al. 2019; Naud et al., 2018; Wall et al., 2018), as well as the local aerosol environment. The large‐scale environment provides the thermodynamic conditions for producing clouds, and the aerosol properties control the detailed processes that determine when and how low‐level clouds precipitate (Savic‐Jovcic & Stevens, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This concerns the microphysical properties of mixed-phase clouds in the ascent regions as well as cirrus clouds in the WCB outflow. Whether changes in NetCRF in a warmer climate are produced by changes in the underlying circulation and availability of moisture or if they are caused by changes in the clouds' microphysical properties remains unclear (Ceppi and Hartmann 2015;McCoy et al 2018). The method of decomposing the climatological signal into a signal produced by an atmosphere without WCBs (C NOWCB ), the contribution from WCBs (WCB effect; C WCB 2 C NOWCB ), and the frequency of WCBs (f WCB ) [see Eqs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Govekar et al (2011) evaluated the distribution of CRF based on satellite data in cyclone composites and showed that the longwave cloud forcing is highest over the warm front where also most of the high cirrus clouds occur. A study by McCoy et al (2018), which is also based on satellite data, showed that stronger moisture inflows enhance the liquid water path in cyclones and thus their shortwave cloud forcing.…”
Section: Introductionmentioning
confidence: 99%